Where you look during golf putting makes no difference to skilled golfers (but what you look at might!): an examination of occipital EEG alpha-power during target and ball focused aiming - Collins, R.; Moffat, D.; Carson, H. J.; Collins, D. (International Journal of Sport and Exercise Psychology, 2023)
This study probed a psycho-motor switch between "attention" and "intention" using electroencephalography (EEG) of the occipital cortex during target versus ball focused aiming when golf putting. Specifically, we investigated (1) the pattern and power of alpha-frequency between putting methods at 8 and 15 ft. distances and (2) the EEG activity for missed versus holed putts. Twelve highly skilled golfers executed 32 putts in total using both methods (i.e., 8 putts per condition) under naturalistic and competitive conditions. Putting performance (number of putts holed and distance from the hole) and EEG activity at -6 s, -4 s and -2 s before movement initiation were recorded. No performance difference was found for holed or missed putts between the putting methods at either distance (p > 0.05). Overall, EEG data revealed a significant time effect, with higher power at -2 s for all conditions apart from at the most challenging 15 ft. distance when using ball focused aiming, where the power decreased. For missed putts at either distance, there was twice the artefact and eye blink during ball compared to target focused aiming. Data suggest a more robust switch from attention to intention when preparing for execution with target focused aiming. Target focused aiming suggestively helps golfers to remove a potential distraction, such as from seeing the arms, hand and ball, rather than offering any distinct/different advantage to ball focused aiming. In other words, a distraction caused by what the golfer looks at rather than where gaze is directed.